2008
DOI: 10.1080/07420520801921572
|View full text |Cite
|
Sign up to set email alerts
|

Light at Night Co‐distributes with Incident Breast but not Lung Cancer in the Female Population of Israel

Abstract: Recent studies of shift-working women have reported that excessive exposure to light at night (LAN) may be a risk factor for breast cancer. However, no studies have yet attempted to examine the co-distribution of LAN and breast cancer incidence on a population level with the goal to assess the coherence of these earlier findings with population trends. Coherence is one of Hill's "criteria" (actually, viewpoints) for an inference of causality. Nighttime satellite images were used to estimate LAN levels in 147 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(143 citation statements)
references
References 48 publications
7
131
2
3
Order By: Relevance
“…Epidemiological studies have shown that melatonin decreases the risk of developing breast and other kinds of cancer (Kliukiene et al, 2001;Kloog et al, 2008;Schernhammer et al, 2008Schernhammer et al, , 2009Schernhammer et al, , 2009Schernhammer et al, , 2010Alpert et al, 2009). However, very little is known about the molecular mechanisms by which melatonin accomplishes its anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that melatonin decreases the risk of developing breast and other kinds of cancer (Kliukiene et al, 2001;Kloog et al, 2008;Schernhammer et al, 2008Schernhammer et al, , 2009Schernhammer et al, , 2009Schernhammer et al, , 2010Alpert et al, 2009). However, very little is known about the molecular mechanisms by which melatonin accomplishes its anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, covering night shift work for 20 years or more has been shown to be notably associated with increased risk of ER-α-related breast cancer [148]. Positive correlation between ALAN intensity (using satellite images) with breast cancer incidences has been clearly demonstrated among Israeli women across 147 communities [149] and also worldwide with approximately 70% and 50% higher risk, respectively, of breast cancer incidences at the highest ALAN intensity compared with the lowest exposure [150]. Furthermore, several observational studies have demonstrated a plausible association between bedroom chronic exposure to moderate levels of ALAN and increased breast cancer prevalence [151][152][153].…”
Section: Circadian Disruption and Breast Cancermentioning
confidence: 95%
“…B 370: 20140120 night accounts for any sizeable proportion of the breast cancer burden in society, then ambient light level as measured by satellite at night should be correlated with breast cancer risk across communities [33]. This has been tested and confirmed within Israel [34], and among 164 countries of the world [35].…”
Section: Diseases Of Modern Lifementioning
confidence: 96%